Trade and Logistics in Central America - Cunha, Barbara; Jaramillo, C. Felipe (World Bank, Washington, DC, 2016)
Central America's trade has increased significantly in the past decade, in great part as a result of strong efforts to reduce tariffs within the region, as well as improvements in market access due to the entry into force of important free trade agreements. However, the growth of Central America's trade has not been as impressive from a global perspective and there is growing evidence that the gains from trade agreements and liberalization policies have been limited by transport and logistics barriers. Studies sponsored by the World Bank reveal that high domestic transportation costs, along with bottlenecks at land border crossings, continue to present large hurdles to intra and extra regional trade. Key factors that impede commerce include the lack of good-quality paved secondary roads, expensive trucking services, and lengthy border crossing procedures. Coordinated efforts to address these bottlenecks could help improve significantly the growth impacts of international trade in the region.